Brand advocacy and repurchase intentions of Malaysian automobile owners - Kwong, Simon C. M. (2013)
In the field of marketing, it is vital that marketers understand the role of advocacy (loyalty intention) and repurchase intention in determining success. The purpose of this research is to determine the factors influencing advocacy and repurchase intention from prospective Malaysian automotive consumers. Specifically, this study focused on, a) the relationships between perceived brand perceptions of value, quality, equity on satisfaction, b) the relationship of satisfaction on commitment, c) the relationship of commitment on advocacy and repurchases intentions and finally d) the influence of “regular auto servicing" and “place of purchase" on customers’ satisfaction. Grounded by The Theory of Reasoned Action (Fishbein and Ajzan, 1967) and The Relationship Marketing Theory (Hunt et al, 2006), this study adopted a research model consisting mainly of “attitudinal” and “behavioral” attributes to study these relationships. The study employed a self-administered, multi- sectioned questionnaire using the purposive sampling methodology with more than 800 respondents from various places within the Klang Valley and lpoh. The multi-sectioned questionnaire employed in this study had different scales which consisted of customer repurchase characteristics of perceived brand perception for quality, value, equity, satisfaction, commitment, advocacy (loyalty intention) and repurchase intention. SEM was used to test the various relationship models. The ﬁndings indicated that, a) equity and quality significantly influenced satisfaction, b) value had no significant impact on satisfaction, c) satisfaction significantly influenced commitment, d) commitment significantly influenced advocacy and repurchase intention and finally e) “regular auto servicing” and “place of purchase" had significant influence on customers‘ satisfaction.